Electromagnetic and thermal modeling of electrical machines for marine applications - Chong, Ming Huei (2014)
With increasing usage of induction motor due to the its reliability and economical reason, not only it is common to be found at home but it is also widely use in marine environment for pumps, compressors etc. However, overheating of the winding can reduce the life span of the induction motor and cause potential danger.